Labor relationship in Viet Nam implementation of EVFTA Agreement - Nguyễn Thị Thanh Thảo (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
EU-Vietnam Free Trade Agreement (EVFTA) is considered as a “new-generation” free trade agreement, which is one of the most ambitious and comprehensive trade agreement that EU signed with a developing country ever. In EVFTA, the labor commitments require Vietnam Government to take a careful consideration in order to adjust the policies, labor laws and regulations and industrial relations. Consequently, the industrial relations in Vietnam would be more solid and efficient.